Cultura empreendedora nas áreas de ciências exatas e tecnológicas da UFSCar - Oliveira, Maísa Maryelli de (2021)
This research is based on the concept of entrepreneurial university and its role in stimulating and supporting student entrepreneurship, especially the knowledge-intensive one, technologically based and with social impact. Fulfilling this role requires the institution to know what students think, their habits, interests, experiences and assessments, in order to develop or adapt initiatives related to entrepreneurship, build dialogues and establish effective actions. Thus, this thesis had the general objective of investigating aspects of the culture of undergraduates at the Center for Exact Sciences and Technology (CCET) of the Federal University of São Carlos (UFSCar), which, by itself and in association with contextual factors, may have influence on their entrepreneurial intention. Regarding the method, it consisted of a predominantly descriptive, qualitative and quantitative research. The procedure adopted for data collection was the online survey and the instrument, a questionnaire, which was applied between August 31st and September 30th, 2020. Participants were defined by accessibility sampling, totaling 173 university students, from 13 undergraduate courses of the CCET at UFSCar, mainly from Engineering degrees. In the analysis of the data collected, qualitative and quantitative variables were used, applying Pearson’s Chi Square Test and Fisher’s Exact Test and the using RStudio software, version 4.0.0 (2020- 04-24). The survey identified students with habits of conversation, information consumption, participation in events and visitation to spaces related to entrepreneurship and showed that there is evidence that these habits are associated with the entrepreneurial intention of undergraduates. But it also revealed that, according to the students’ perception, UFSCar hardly contributes to feeding and maintain such habits and experiences. The dialogues about entrepreneurship take place predominantly with parents, family and friends, institutional channels are rarely consulted as a source of information and the events in which students participate take place mainly outside the academy. Despite the sense that there is an institutional scenario of little incentive, 41% of respondents intend to start their own business after graduation and, of these, 74.6% are considering creating a technology-based company and/or startup, having as themes of interest those fundamentally related to the generation of social and environmental impact, such as: smart and sustainable cities, creative economy, circular economy and education. We conclude, based on the discussion of the results achieved, that it was possible to advance in the understanding of how an entrepreneurial university can both improve its actions of attraction, training and support, as well as educate undergraduates for an ethical, solidary, collaborative and responsible entrepreneurial performance, by investigating students’ perceptions on five dimensions: 1) Education and training; 2) Entrepreneurial ability; 3) Cultural and social norms; 4) Structure and information; and 5) Science, Technology, Entrepreneurship and Society.